LEGAL SOCIALIZATION OF PERSONALITY IN THE ERA OF ELECTRONIC COMMUNICATION - Біленчук, Петро Дмитрович; Ланцедова, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Review of the collective monograph "Legal socialization of the individual in the modern world: man, society, civilization" edited by O.L. Kobylyansky.